PEMBERDAYAAN PENGELOLA PASAR DESA PAKRAMAN PANJER DALAM DETEKSI DINI PENYAKIT TIDAK MENULAR - Jirna, I Nyoman; Sudarmanto, I Gede; Suyasa, I Nyoman Gede (Poltekkes Kemenkes Denpasar, 2025)
Pakraman Panjer Village Market is the economic center of the Panjer traditional village located on Jalan Pakerisan Denpasar Bali. The results of the initial survey of 10 traders showed that the problem was that 50% of traders had low activity levels, 10% had a heavy physical appearance and tended to be obese, 50% were in the elderly category, 30% consumed foods high in cholesterol and carbohydrates/sugar, 10% were active smokers, 60% had a level of knowledge. low, 10% routinely carry out early examinations. This data shows that the targeted 100% health services/screening and early detection of NCD risk factors have not been achieved.The service method is in the form of counseling, training, empowerment, checking PTM (cholesterol, glucose, uric acid, blood pressure) for traders and market managers in Pakraman Panjer village. Partner's contribution as a role model through cadres formed for the sustainability of this Community Service activity.There was an increase in knowledge from 50 targets before and after counseling, namely 30 people (60%). an increase in normal cholesterol in 8 people (16%) s, an increase in normal glucose in 8 people (16%), an increase in uric acid in 8 people (16%) and an increase in normal blood pressure in 13 people (26%) before and after coaching. As a result of coaching 10 market managers, there was an increase in their ability as instructors, namely 6 people (60%) to 9 people (90%).Extension workers formed from market managers carry out continuous guidance to traders and related agencies (puskesmas) provide assistance and supervision.Keywords:. Empowerment, Early Detection, Non-Communicable Diseases,